MENEMUKAN RUANG KETIGA DALAM DAKWAH ANTARBUDAYA (Analisis Cultural Studies sebagai Kritik atas Gerakan Dakwah Puritanisme) - Puji Laksono (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2017)
Dakwah in Islam is a divine task performed by each individual and collectively to its adherents. Dakwah has a goal to invite people to the path of goodness and instructions for obtaining happiness of the world and the hereafter. Practice dakwah that accompanied the business domination and cultural imperialism as did the puritans will only lead to dissociative interaction processes of intercultural, which leads to a clash of cultures, conflicts and contradictions. It is certainly far from ideal destination dakwah. Thus, the sociological aspect in the implementation of dakwah is also worth noting, that not only makes the community as an object, but also should pay attention to the community as a subject of dakwah. Which not only makes the community as an object, but also should pay attention to the community as a subject of dakwah. Side of the subjectivity of society is cultural identity. Implementation of dakwah should be accompanied by an understanding of the cultural differences that practiced by the community to find a third space that is dialogical in intercultural dakwah.